Exploring the Influence of Gender on Cassava (Manihot esculenta) Value Chain among Smallholder Farmers: A Case of Central Highlands, Vietnam - Ao Xuan Hoa; Vo Xuan Hoi; Duong Minh Ngoc; Nguyen Thi Huynh Nha; Vu Trinh Vuong (My University, 2023)
Exploring the Influence of Gender on Cassava (Manihot esculenta) Value Chain among Smallholder Farmers: A Case of Central Highlands, Vietnam
Keywords: Gender influence